Obstetric physiotherapy from the perspective of high-risk pregnant women admitted to a high-complexity maternity (Research, Society and Development, 2024)
Objective: To analyze the perception of hospitalized pregnant women about the importance of obstetric physiotherapy in a reference public maternity hospital, as well as to identify the contribution of physiotherapy to the evolution of pregnant women during the hospitalization process. Methods: This is an observational, cross-sectional, and descriptive study, with a quantitative approach, carried out with 31 high-risk pregnant women over 18 years of age, hospitalized in a highly complex public reference maternity hospital. For data collection, a questionnaire on socio-personal characterization and obstetric physiotherapy was used, containing 26 easy-to-solve questions. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 21.0. The significance level adopted was p-value